The poetics of glass in France, 1850-1900 - Ryan, N (2016)
This thesis examines the representation of glass in French and Belgian poetry associated with the Symbolist and Decadent movements. It incorporates a number of authors, particularly focussing on Baudelaire, Mallarmé, Laforgue, Rodenbach, and Maeterlinck, but also encompassing more minor writers where appropriate, as well as some writers on the periphery of Symbolism and Decadence. The thesis investigates how the growing use of glass in architecture, technology, and visual art influenced late-nineteenth-century poets, providing these writers with a means by which to understand their social context as well as a multi-faceted metaphor through which to interrogate their own poetic mechanisms. Glass, in its various manifestations – windows, lenses, hothouses, aquariums, Exhibition halls, Art Nouveau glasswork, and stained glass – prompts meditation on such questions as: the interaction between subject and object; the relationship between fiction and reality; the infinite; poetic form; nature and artifice; and aesthetic identity. Ultimately, I combat the traditional understanding of this poetry as being solely concerned with the pure realm of dreams, the soul, and the 'Idée'. Instead, I insist on the material world as a starting point for this poetry, demonstrating that it is not immune to environmental factors, but rather that it uses its environment as a route towards the elusive 'Idée'. Glass is key to this process because its very ambiguity makes it a suitable embodiment of the tension between the material and the unknown, invisible, or ideal.